Plant bioactive compounds: extraction, biological activities, immunological, nutritional aspects, food application, and human health benefits—A comprehensive review - El-Saadony, Mohamed T.; Saad, Ahmed M.; Mohammed, Dina Mostafa; Alkafaas, Samar Sami; Abd El-Mageed, Taia A.; Fahmy, Mohamed A.; Ezzat Ahmed, Ahmed; Algopishi, Uthman Balgith; Abu-Elsaoud, Abdelghafar Mohamed; Mosa, Walid F. A.; AbuQamar, Synan F.; El-Tarabily, Khaled A. (Frontiers in Nutrition, 2025)
In recent years, there has been a growing awareness of the importance of a nutritious diet for maintaining overall health. Among dietary components, plant-derived bioactive compounds have garnered significant attention due to their functional properties and potential to prevent various diseases. These bioactive constituents, although typically present in small quantities, provide substantial health benefits and are considered non-nutritive yet physiologically active components of the diet. Medicinal plants, vegetables, fruits, cereals, sauces, and spices have become focal points in nutritional research, owing to their diverse array of bioactive compounds. These compounds, including polyphenols, glucosinolates, carotenoids, terpenoids, alkaloids, saponins, vitamins, and dietary fibers, are increasingly recognized for their ability to reduce the risk of chronic diseases, as demonstrated by epidemiological studies. These molecules exhibit a broad spectrum of therapeutic activities, including antioxidant, anti-inflammatory, anti-atherogenic, antimicrobial, antithrombotic, cardioprotective, and vasodilatory activities. Despite their promising pharmacological and nutritional potential, the integration of plant-derived bioactive compounds into commercial products remains limited. Importantly, bioactive compounds that possess antioxidant and antimicrobial activities are increasingly acknowledged for their potential application as natural and environmentally sustainable food preservatives. The expanding interest in these applications underscores the critical need for efficient and standardized extraction methods. While conventional extraction techniques have been widely used, they often suffer from limitations such as low yield, degradation of heat-sensitive compounds, and high solvent consumption. To address these challenges, innovative and integrated extraction technologies have been developed, offering advantages such as enhanced extraction efficiency, reduced impurities, and lower environmental impact. These methods often employ reduced solvent use and energy input, aligning with sustainability goals. This review aims to provide a comprehensive overview of bioactive plant compounds by examining their extraction methods, biological and immunological activities, nutritional significance, food applications, and health benefits for humans.